Ionization energies of germanium-doped AlxGa1-xAs epilayers grown on GaAs substrates - Kim, HJ; Park, YK; Kim, SI; Kim, YT; Kim, EK; Moon, S; Kim, TW (KOREAN PHYSICAL SOC, 1999)
Photoluminescence (PL) measurements on germanium (Ge)-doped AlxGa1-xAs have been performed to investigate the ionization energy of Ge in AlxGa1-xAs. PL spectra at room temperature showed one peak for all Al mole fractions. On the other hand, PL spectra at a temperature of 77 K showed one peak for Al mole fractions of less than 0.06, and four peaks for Al mole fractions of larger than 0.1. The energy difference between the highest and the second highest peak energies indicated the ionization energy of Ge in AlxGa1-xAs. The experimental results were compared with the theoretical results, which were calculated by a simple effective mass model. A broad emission peak near 1.5 eV with full width at half maxima of about 80 similar to 100 meV was observed for an alloy composition of x greater than or equal to 0.108 at 77 K. These results suggest that the broad emission peak might originate from the Ge acceptor-As vacancy donor pair.
Keywords: CHEMICAL-VAPOR-DEPOSITION; PHOTOLUMINESCENCE; CRYSTALS; EPITAXY